Evidence for a sliding-resistance at the tip of the trypanosome flagellum. - Woolley, D; Gadelha, C; Gull, K (2006)
Motility in trypanosomes is achieved through the undulating behaviour of a single "9 + 2" flagellum; normally the flagellar waves begin at the flagellar tip and propagate towards the base. For flagella in general, however, propagation is from base-to-tip and it is believed that bend formation, and sustained regular oscillation, depend upon a localised resistance to inter-doublet sliding - which is normally conferred by structures at the flagellar base, typically the basal body. We therefore predicted that in trypanosomes there must be a resistive structure at the flagellar tip. Electron micrographs of Crithidia deanei, Herpetomonas megaseliae, Trypanosoma brucei and Leishmania major have confirmed that such attachments are present. Thus, it can be assumed that in trypanosomes microtubule sliding at the flagellar tip is resisted sufficiently to permit bend formation.